1997
DOI: 10.1209/epl/i1997-00388-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubules of bare boron clusters: Ab initio and density functional study

Abstract: Using ab initio quantum-chemical and density functional methods we have determined novel structures of bare boron clusters. In addition to previously reported quasi-planar, convex and spherical cluster forms, boron nanotubules seem to be highly stable as well. These novel nanotubular structures are composed of hexagonal pyramids only and can be considered as segments of extended pipes. Applying a previously reported "Aufbau Principle", one can easily construct stable boron structures besides the new nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
129
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 19 publications
7
129
1
Order By: Relevance
“…Although the natural phases of bulk boron do not possess laminar structures, recent experimental studies [8] confirmed the existence of quasiplanar clusters of 10-15 B atoms which have been previously predicted by first principle calculations [9]. Furthermore, single walled boron nanotubes (SWBNTs) have also been declared beforehand by Boustani and coworkers [10][11][12][13] which have also been synthesized experimentally [14,15] a few years ago with a radius of nearly 18Å, after the fabrication of crystalline [16] and amorphous [17] boron nanowires with diameters as small as 20 nm. A recent review article about boron nanotubes which may serve as a basic orientation for any reader interested in pure boron chemistry can be found in [18].…”
Section: Introductionmentioning
confidence: 63%
“…Although the natural phases of bulk boron do not possess laminar structures, recent experimental studies [8] confirmed the existence of quasiplanar clusters of 10-15 B atoms which have been previously predicted by first principle calculations [9]. Furthermore, single walled boron nanotubes (SWBNTs) have also been declared beforehand by Boustani and coworkers [10][11][12][13] which have also been synthesized experimentally [14,15] a few years ago with a radius of nearly 18Å, after the fabrication of crystalline [16] and amorphous [17] boron nanowires with diameters as small as 20 nm. A recent review article about boron nanotubes which may serve as a basic orientation for any reader interested in pure boron chemistry can be found in [18].…”
Section: Introductionmentioning
confidence: 63%
“…4 But also in other structures, uncommon bonding situations are found, so the whole series of boranes and borates are not properly described by Lewis structures but by concepts developed by Lipscomb, Wade, and Williams. 5−8 In addition to these fascinating molecular systems, stable quasi-planar and tubular clusters of elemental boron were first predicted 9,10 and later observed experimentally. 11 −13 On the basis of these findings, the existence of more complex pure boron nanostructures like boron fullerenes, 14,15 nanotubes, and two-dimensional sheets has been predicted.…”
Section: Introductionmentioning
confidence: 99%
“…We describe a simple and clear picture of electronic bonding in boron sheets and highlight the importance of three-center bonding and its competition with two-center bonding, which can also explain the stability of recently discovered boron fullerenes. Our findings call for reconsideration of the literature on boron sheets, nanotubes and clusters.PACS numbers: 73.63.Fg All boron nanotubes (BNT), regardless of diameter or chirality, are predicted to be metallic and have large densities of states (DOS) at their Fermi energies (E F ) [1]. In contrast, carbon nanotubes (CNT) can be semiconductors or metals with small DOS at their E F .…”
mentioning
confidence: 99%
“…PACS numbers: 73.63.Fg All boron nanotubes (BNT), regardless of diameter or chirality, are predicted to be metallic and have large densities of states (DOS) at their Fermi energies (E F ) [1]. In contrast, carbon nanotubes (CNT) can be semiconductors or metals with small DOS at their E F .…”
mentioning
confidence: 99%